Three Dimensional Structure of Human Fibrinogen under Aqueous Conditions Visualized by Atomic Force Microscopy - Marchant, Roger E; Barb, Matthew D; Shainoff, John R; Eppell, Steven J; Wilson, David L; Siedlecki, Christopher A (Thrombosis and Haemostasis, 1997)
Fibrinogen plays a central role in surface-induced thrombosis. However, the interactions of fibrinogen with different substrata remain poorly understood because of the difficulties involved in imaging globular proteins under aqueous conditions. We present detailed three dimensional molecular scale images of fibrinogen molecules on a hydrophobic surface under aqueous conditions obtained by atomic force microscopy. Hydrated fibrinogen monomers are visualized as overlapping ellipsoids; dimers and trimers have linear conformations predominantly, and increased affinity for the hydrophobic surface compared with monomeric fibrinogen. The results demonstrate the importance of hydration on protein structure and properties that affect surface-dependent interactions.